How to Reject Any Scientific Manuscript - GERNERT, DIETER (Journal of Scientific Exploration, 2010)
After a short overview of arguments pro and contra peer reviews, examples of gross misjudgement are compiled, followed by an attempt to identify some frequent, recurrent patterns of unjustified rejection of scientific manuscripts. A few specific questions are studied in more detail: the claim for still more precise and comprehensive definitions, the right way of handling ‘‘parallel theories’’, and the frequent misuse of the term ‘‘pseudoscience’’. Finally, practical rules to improve refereeing and ‘‘basic rights of authors’’ are proposed, together with a word of encouragement for future authors. Keywords: Peer reviews—cases of misjudgement—patterns of unjustified rejection—misuse of the term ‘‘pseudoscience’’—proposals to improve refereeing